2005
DOI: 10.1007/s00198-005-1909-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and fracture risk in type-2 diabetes mellitus: the Rotterdam Study.

Abstract: The aim of this study was to determine the association between type-2 diabetes mellitus (DM), BMD and fractures in 6,655 men and women aged 55 years and over from the Rotterdam Study. We compared subjects with type-2 DM to subjects without DM. Additionally, subset analyses were performed, dividing subjects on the basis of the glucose tolerance test into already treated DM, newly diagnosed DM, impaired glucose tolerance (IGT) and normal glucose tolerance (NGT, reference). Femoral neck and lumbar spine BMD were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
299
2
26

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(356 citation statements)
references
References 38 publications
14
299
2
26
Order By: Relevance
“…The Rotterdam study included 792 elderly individuals with type II diabetes mellitus and 5863 non-diabetic controls, and it found a hazard ratio of 1.33 (95% CI 1.00-1.77) for fractures in the diabetic group. 21 In addition, the Rancho Bernardo Study reported that metabolic syndrome was not only associated with a lower BMD, but it was also associated with an increased incidence of osteoporotic fractures. 22 Hyperglycemia may have a direct adverse effect on bone metabolism because glucose enhances osteoclast activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The Rotterdam study included 792 elderly individuals with type II diabetes mellitus and 5863 non-diabetic controls, and it found a hazard ratio of 1.33 (95% CI 1.00-1.77) for fractures in the diabetic group. 21 In addition, the Rancho Bernardo Study reported that metabolic syndrome was not only associated with a lower BMD, but it was also associated with an increased incidence of osteoporotic fractures. 22 Hyperglycemia may have a direct adverse effect on bone metabolism because glucose enhances osteoclast activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Alternatively, analyses of bones of type 2 diabetics have generally observed unchanged or increased bone mineral density, though clinically, both diabetic populations have a substantially increased risk of fractures in comparison to non-diabetics. 18,[21][22][23][24] Additionally, there is increasing evidence that some diabetic medications may negatively impact bone density and marrow adiposity. 1,[25][26][27][28][29] Diabetes also induces microvascular remodeling in the bone marrow manifesting as impaired angiogenic ability, vascular endothelial cell dysfunction, and a reduction in stem cell number.…”
Section: Diabetes and Its Complicationsmentioning
confidence: 99%
“…There is also increasing evidence supporting an association between type 2 diabetes and increased fracture risk (2)(3)(4). The Rotterdam study revealed that individuals with type 2 diabetes had a 69% increased fracture risk compared with those without diabetes, despite having higher BMD (5). In addition, impaired fracture healing is also demonstrated in diabetes (2)(3)(4)6,7).…”
Section: Introductionmentioning
confidence: 99%